Right heart pressure determination by Doppler in infants with tricuspid regurgitation. Issue 2 (August 1993) - Skinner, J R; Stuart, A G; O'Sullivan, J; Heads, A; Boys, R J; Hunter, S
Abstract : Doppler and direct measurements of right ventricle to right atrial pressure drop were made during cardiac catheterisation on 28 occasions in 26 infants with congenital heart disease. Age was 10 days to 12 months (median 4.5 months), and weight was 3.1 to 9.0 kg (median 4.7 kg). We measured peak velocity of tricuspid regurgitation by continuous wave Doppler, and the pressure drop was calculated using the modified Bernoulli equation (delta p = 4v2). There was a high correlation (r = 0.95) between direct and Doppler measurements. Doppler values tended to underestimate the right ventricle to right atrial pressure drop, but this was not of clinical significance (mean 2 mm Hg). The 95% confidence interval for the Doppler velocity was -0.41 to +0.26 m/sec, and was consistent across the range of pressures studied. Variability between observers was tested, by two observers performing sequential paired examinations on 16 newborn babies with tricuspid regurgitation. The coefficient of repeatability was 6.3 mm Hg (95% confidence interval 4.7 to 9.5 mm Hg) or 0.26 m/sec (0.18 to 0.50 m/sec). This method of right ventricular pressure estimation, validated previously only in older children and adults, is a reproducible and accurate technique in infants with tricuspid regurgitation.